Methodology optimization to quantify microplastic presence in planktonic copepods, chaetognaths and fish larvae - S.M. Rodrigues; F. Espincho; M. Elliott; C. Marisa R. Almeida; S. Ramos (MethodsX, 2023)
Two of the groups most impacted by microplastics (MPs) are zooplankton and fish larvae, either through MPs ingestion or absorption. Although there has been an increase of studies focusing on MPs ingestion by these organisms, there is still no standardized methodology for the quantification of MPs present in plankton. For example, some reagents normally used to digest plankton and recover MPs appear adversely to affect some plastic characteristics. This can potentially lead to underestimating the amount and types of MPs present in the organisms analyzed. Hence, this work aimed to optimize a methodology to quantify MPs present in plankton, namely zooplankton and fish larvae, and ensuring MPs integrity. Hence, the planktonic organism tissues were digested using 30% (v/v) H2O2 solution at different temperatures and incubation periods while preserving the integrity and polymer characteristics of 13 types of MPs. MPs’ characteristics were register before and after the tests, by visual inspection and Fourier Transform Infrared Spectroscopy (FTIR) analysis, to evaluate the integrity and features of MPs. With this methodology, MPs recovery was above 85% for all types of plastic tested. The proposed methodology is a rapid protocol, with a maximum of 7 h of incubation, that ensures simultaneously the full digestion of the organism tissues and the complete preservation of all the plastic characteristics, namely color, size and polymer type. • A methodology was optimized to quantify microplastics present in zooplankton (copepods, chaetognaths and fish larvae). • Thirteen types of microplastics (fibers and fragments of different polymers) were used to test the efficiency of the methodology ensuring the maintenance of the integrity of plastics. • With this methodology, microplastic recovery was above 85% for all the types of microplastic tested and no changes in their characteristics were observed.